Welfare Benefits of Agglomeration and Worker Heterogeneity - Coen Teulings; Ioulia Ossokina; Henri L.F. de Groot (Tinbergen Institute, 2014)
The direct impact of local public goods on welfare is relatively easy to measure from land rents. However, the indirect effects on home and job location, on land use, and on agglomeration benefits are hard to pin down. We develop a spatial general equilibrium model for the valuation of these effects. The model is estimated using data on transport infrastructure, commuting behavior, wages, land use and land rents for 3000 ZIP-codes in the Netherlands and for three levels of education. Welfare benefits are shown to differ sharply by workers' educational attainment.
Keywords: H04; H54; R13; R23; R04; 330; local public goods; agglomeration; spatial equilibrium; residential sorting; land rents